Association of endothelial nitric oxide synthase (enos) gene polymorphisms and physical fitness levels with plasma nitrite concentrations and arterial blood pressure values in older adults - Da Silva, Roberta Fernanda [UNESP]; Trapé, Á Tila Alexandre; Reia, Thaís Amanda [UNESP]; Lacchini, Riccardo; Oliveira-Paula, Gustavo Henrique; Pinheiro, Lucas Cezar; Tanus-Santos, José Eduardo; Jacomini, André Mourão [UNESP]; Jú Nior, Carlos Roberto Bueno; Zago, Anderson Saranz [UNESP] (Public Library of Science (PLoS), 2018)
Endothelial nitric oxide synthase (eNOS) gene polymorphisms are associated with reduced eNOS activity and nitric oxide (NO) production leading to an increase in blood pressure (BP). Regular exercise is the main strategy to minimize the deleterious effects of polymorphisms. However, due to the differences that physical exercise can be performed, some controversial results are found. Therefore it seems reasonable to evaluate the training status (TS). Thus, this study aimed to investigate the association of eNOS gene haplotypes and different levels of TS on nitrite concentrations (NO2-) and BP values in older adult. 424 elderly performed the following assessments: General Functional Fitness Index (GFFI) to estimate TS, systolic and diastolic blood pressure (SBP and DBP), blood collection for analysis of NO2-and g.-786T>C, intron 4b/a (VNTR) and 894G>T polymorphisms. Multivariate logistic regression showed that NO2-was influenced by GFFI and 4b/4a Intron 4. RegardingBP, GFFI influenced SBP and DBP, and just intron 4 was associated with variations in DBP. It can be observed that GFFI affected the NO2-, SBP and DBP independently of haplotypes. Therefore, maintenance of good level of TS can overcome the negative influence of genetics factors (intron 4) by increasing NO2-concentration and decreasing BP values.